The Implementation of the Four Strands Model in Teaching Arabic Fusha to Arabic Education Students - Firman Alamsyah; Maksudin Maksudin; Abdul Kahfi Amrulloh (Tadris Al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2026)
Arabic language learning in higher education still faces challenges, particularly in students’ speaking fluency and vocabulary mastery. Studies on the implementation of the Four Strands model in Arabic fuṣḥā learning remain limited, especially in higher education contexts. This study aims to describe the implementation of the Four Strands model proposed by Paul Nation in the Al-Lughah Al-‘Arabiyyah Al-Fuṣḥā course at STAI Masjid Syuhada Yogyakarta. The study employed a descriptive qualitative approach, with data collected through observation, interviews, questionnaires, and documentation. Data were analyzed using the Miles dan Huberman model. The results indicate that the four components of the Four Strands were integrated into the learning process, with an increase in the average score from 67.6 to 75.1. The uniqueness of this study lies in the comprehensive implementation of the Four Strands model in the context of Arabic fuṣḥā learning. This study contributes to the development of more communicative Arabic language learning in higher education.